The Influence of Position Promotion and Work Autonomy on Performance in the Bondowoso Regency Civil Service Police Unit - Pamungkas, Herfin Andiansyah; Qomariah, Nurul; Susbiyani, Arik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Competition in the business world is increasing. Every organization is required to continue to improve employee performance, whether it is a government-owned or private organization. This research aims to analyze and determine the effect of promotion and work autonomy on the performance of the Bondowoso Regency Civil Service Police Unit. The population in this study were all employees in the Bondowoso Regency Civil Service Police Unit, totaling 145 employees. Meanwhile, the sample size was determined on the basis of purposive sampling based on employees who fall into the ASN (State Civil Servant) category, totaling 85 employees. Descriptive analysis was carried out to determine the respondents' descriptions and research variables. Validity tests and reliability tests were also carried out to test research measuring instruments. Hypothesis testing is carried out to test the influence of the independent variable on the dependent variable. The results of the research show that promotion and work autonomy have a positive and significant impact on employee performance in the Bondowoso Regency Civil Service Police Unit.